2022
DOI: 10.3390/sports10020013
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Investigation into the Talent Development Processes in an English Premiership Rugby Union Academy: A Preliminary Study through an Ecological Lens

Abstract: (1) Background: The progression of youth rugby union (RU) players towards senior professional levels can be the result of various different constraints. The aim of this study was to examine characteristics that differentiated playing positions and player rankings in an English Premiership RU academy. (2) Methods: Thirty players (mean age = 18.5 ± 2.8 years) were divided by playing positions (forwards = 18, backs = 12) and ranked (one to thirty) by coaches based on their potential to achieve senior professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The present findings are in line with a recent multi-disciplinary work on an English Premiership RU academy, which demonstrated that greater exposure to different activities during childhood and early adolescence had a positive impact on higher player rankings (58). Curiously, coaches did not argument the possibility that some activities could be better than others (i.e., deliberate play vs. deliberate practice) for players progression, thus it seems that this factor do not impact significantly upon the talent path.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings are in line with a recent multi-disciplinary work on an English Premiership RU academy, which demonstrated that greater exposure to different activities during childhood and early adolescence had a positive impact on higher player rankings (58). Curiously, coaches did not argument the possibility that some activities could be better than others (i.e., deliberate play vs. deliberate practice) for players progression, thus it seems that this factor do not impact significantly upon the talent path.…”
Section: Discussionsupporting
confidence: 92%
“…Both players and coaches believed psychological and psychosocial characteristics to be part of a holistic set of pivotal characteristics for TID and TD in RU, which aligns with recent findings in sport psychology (11,58,66). In particular, the recognised capacity of working hard (from PG1, PG2, and CG), having the right mindset (from PG1 and PG2), possessing a strong work ethic (i.e., a set of values centred on the importance of doing work and reflected especially in a desire or determination to work hard; from CG only), and the capacity of asking for feedback (from PG1, PG2, and CG) were viewed as fundamental behavioural characteristics to become a professional RU player in the present academy.…”
Section: Discussionsupporting
confidence: 83%
“…It is also important to consider how articles can be grounded or discussed through relevant models or theories (e.g., [19,20]). As a novel example, Kelly and colleagues [21] used the Personal Assets Framework to explain the immediate, short-term, and long-term developmental outcomes due to relative age effects in English male cricket.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…With regards to applied nuances, the ecological dynamics-based framework has demonstrated itself popular within talent development research for its pertinent emphasis of multivariable effects [e.g., ( 102 )]. It is proposed that no single independent factor can account for real-world differences in performance; instead, it is the combination of task (e.g., practice history), organism (e.g., anthropometrics and technical/tactical awareness), and environmental (e.g., relative age and sociocultural) constraints ( 73 ).…”
Section: Future Research Directionsmentioning
confidence: 99%